2016
DOI: 10.1016/j.vaccine.2016.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Re-designing the Mozambique vaccine supply chain to improve access to vaccines

Abstract: Introduction Populations and routine childhood vaccine regimens have changed substantially since supply chains were designed in the 1980s, and introducing new vaccines during the “Decade of Vaccine” may exacerbate existing bottlenecks, further inhibiting the flow of all vaccines. Methods Working with the Mozambique Ministry of Health, our team implemented a new process that integrated HERMES computational simulation modeling and on-the-ground implementers to evaluate and improve the Mozambique vaccine supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 9 publications
2
59
0
Order By: Relevance
“…Of course, the impact may vary depending on the severity of constraints in a supply chain and the burden of disease in the population. However, as previous studies have shown, many lower- and middle-income counties suffer from significant bottlenecks[13, 11, 12], while the burden of major vaccine-preventable disease remains high[13]. …”
Section: Discussionmentioning
confidence: 99%
“…Of course, the impact may vary depending on the severity of constraints in a supply chain and the burden of disease in the population. However, as previous studies have shown, many lower- and middle-income counties suffer from significant bottlenecks[13, 11, 12], while the burden of major vaccine-preventable disease remains high[13]. …”
Section: Discussionmentioning
confidence: 99%
“…As described in previous publications,7 9 10 13–16 Highly Extensible Resource for Modelling Event-Driven Supply Chains (HERMES) is a software platform developed by the HERMES logistics team that allows users to generate detailed discrete event simulation models of any vaccine supply chain. Each supply chain model contains a virtual representation of all storage facilities and devices (including buildings, refrigerators and freezers), vehicles and routes (including vehicle types, travel frequency and travel distance), human resources (including logisticians, drivers and vaccinators), vaccines, supply chain policies and associated costs for each component.…”
Section: Methodsmentioning
confidence: 99%
“…As our previous studies demonstrated, the design of most low-income and middle-income countries’ routine immunisation systems took place around four decades ago 5–8. Despite changes in external circumstances (eg, substantial population growth) and the introduction of new technology (eg, vaccine introductions), there have been relatively few re-design efforts until recently 5 9 10. This raises the possibility that significant coping could be occurring.…”
Section: Introductionmentioning
confidence: 99%
“…Our team used three previously developed stochastic, discrete-event vaccine supply chain simulation models of Benin [16] , [17] , [18] , Bihar [19] and Mozambique [20] . These models were developed using the Highly Extensible Resource for Modeling Supply Chains (HERMES) software and virtually represent all of the storage facilities, refrigerators and freezers, shipping routes, vehicles, personnel, and vaccines in each supply chain.…”
Section: Methodsmentioning
confidence: 99%